Impact of Legalized Gambling on Gambling Behaviour and Monetary Benefits to the State Government : Evidence of Trade-off from Sikkim - Rai, Adarsh; Murari, Krishna (Prabandhan: Indian Journal of Management, 2020)
A high rate of prevalence of problem gambling represents an urgent public health issue in many countries. Excessive gambling behaviour of a gambler not only affects the gambler, but it also affects and influences his/her family and the life of the people living around him/her. This paper aimed to identify the prevalence of problem gambling among the gamblers of Sikkim and highlight the amount of revenue generated from the casino industry and the state lotteries in Sikkim. The prevalence of problem gambling was identified using the Problem Gambling Severity Index. Based on the scores of the Problem Gambling Severity Index, 26.3% of the gamblers in Sikkim were categorized as problem gamblers and 47.5% of them were categorized as moderate-risk gamblers. In terms of revenue generation, from the period between 2011–12 and 2017–18, the Government of Sikkim generated revenue of about ₹2,274 million from its state lottery and ₹350.46 million from its casino industry. Although the revenue generated from the gambling industry in Sikkim is increasing, the high rate of prevalence of problem gambling is a matter of great concern.